A technique for marking oncological breast tissue specimens. (May 2016) - Patel, Jaison; Jenkins, Stephanie
Abstract: With new breast conserving oncological surgical techniques, accurate identification of specimen margins is important to allow for the re-excision of margins. The accurate identification of margins is crucial is the success of the patients treatment if further margins are required. NHS Breast Screening Programme (NHSBSP) guidelines recommend the excised specimen is labelled accurately to correctly identify the margins and allow for X-ray examination. This method has been proven to be cheap, it uses equipment and materials readily available in the operating theatre. Furthermore, if any of the methods fails as there is more than one way to identifying your margins. For example if a clip were to fall off, the type/length of suture and the orientation on the board will still allow you to identify the correct margin. If the sample was to fall off the board, the sutures and clips will still allow the pathologist to orientate the sample. In summary this method is easy to apply, logical and uses equipment readily available within the theatre, i.e. silk sutures, and the needle protection board. It ensures all relevant radiological and surgical criteria are met for enabling orientation of the specimen when removed from the breast tissue. It is an easily taught technique that is easy to remember. A national survey showed a lack and wide variation of specimen orientation protocols. (Volleamere et al., 2013) This technique could be used as the national standard for breast specimen marking and as a national marking system for the NHS. Highlights: There is a variation in the techniques used to mark breast specimens. There is no national standard to how specimens should be marked. The identification of margins is essential if re-excision of margins is required. Specimen marking should be compatible for both radiological and pathological analysis. The technique should be easy to remember and easily taught and understood by clinicians.